2016
DOI: 10.1186/s12939-016-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and knowledge gaps on the disease burden in sexual and gender minorities: a review of systematic reviews

Abstract: Sexual and gender minorities (SGM) include individuals with a wide range of sexual orientations, physical characteristics, and gender identities and expressions. Data suggest that people in this group face a significant and poorly understood set of additional health risks and bear a higher burden of some diseases compared to the general population. A large amount of data is available on HIV/AIDS, but far less on other health problems. In this review we aimed to synthesize the knowledge on the burden of communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 46 publications
(111 reference statements)
2
65
0
3
Order By: Relevance
“…A review of systematic reviews showed that sexual and gender minorities are highly burdened by human immunodeficiency virus infection, sexually transmitted infections, sexually transmitted infection-related cancers, mental health conditions and violent experiences 105 . We suggest further research into the associations of violence motivated by perception of sexual orientation and gender identity with adverse health and social outcomes, including criminalization.…”
Section: Discussionmentioning
confidence: 86%
“…A review of systematic reviews showed that sexual and gender minorities are highly burdened by human immunodeficiency virus infection, sexually transmitted infections, sexually transmitted infection-related cancers, mental health conditions and violent experiences 105 . We suggest further research into the associations of violence motivated by perception of sexual orientation and gender identity with adverse health and social outcomes, including criminalization.…”
Section: Discussionmentioning
confidence: 86%
“…In relation to conversion therapy, health professionals’ assumptions framing LGBT identities as ‘disorders’ were based on dated diagnoses that were removed from the psychiatric systems of diagnosis and classification (DSM and ICD) as part of the demedicalization of sexual orientation . This lack in knowledge supports the need for education and training of health professionals widely reported in research to question normativity and promote more inclusive health‐care practices for LGBT people . Health professionals will benefit from further education and training to help them navigate their way through changing terminology and complex health‐care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Health inequalities are documented in a range of areas including increased rates of HIV and STIs in gay, bisexual and other men who have sex with men . Also, reviews of studies on weight discrepancies in LGB people showed a higher risk of raised weight increasing sequentially with age .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated risk of tobacco use among LGBT individuals has been attributed to LGBT targeted tobacco product marketing [4,[9][10][11][12] and minority stress (ie, strain resulting from stigma and discrimination associated with having a minority identity) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%